A theoretical study of family resource management - Yadollahi, Mehdi; Paim, Laily (Marsland Press, 2011)
Family resource management has a fundamental role in helping meet and alter the increasing complexities faced by the families. In this way, this article attempts to describe the theories of family economic management. To solve the economic problems we need to improve the economic status of families who fail to manage their budget, which results in high debt levels and a lack of personal savings. The implication of this study arises from the fact that there has been little research carried out on the family economic status. Theoretically, the findings of this study enrich the knowledge concerning family economic and management functions.